2016
DOI: 10.1038/srep36627
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of nanoscale metallic glasses during high-pressure torsion: A molecular dynamics analysis

Abstract: Structural evolution in nanoscale Cu50Zr50 metallic glasses during high-pressure torsion is investigated using molecular dynamics simulations. Results show that the strong cooperation of shear transformations can be realized by high-pressure torsion in nanoscale Cu50Zr50 metallic glasses at room temperature. It is further shown that high-pressure torsion could prompt atoms to possess lower five-fold symmetries and higher potential energies, making them more likely to participate in shear transformations. Meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Above the critical size, the increase in correlation length decreases the number of soft clusters, limiting strain percolation paths to form shear bands, intensifying the extent of strain localization and reducing the ductility of MGs. Since the population of soft spots and their spatial distribution can be tuned by such processes as rapid quenching, 14 high-pressure torsion, [55][56][57] laser processing, 58 and mechanical cycling, 59 and magnetization, 60 we envision that our results may offer a totally new approach of using the control of short-range to medium-range order in monolithic MGs to radically improve the ductility, and hence the fracture toughness, of these alloys. As such, this may provide new possibilities for the industrial application of these high-strength metallic alloys as structural materials with unique combinations of mechanical properties.…”
Section: A Transition In Shear-band Formation Mechanismsmentioning
confidence: 98%
“…Above the critical size, the increase in correlation length decreases the number of soft clusters, limiting strain percolation paths to form shear bands, intensifying the extent of strain localization and reducing the ductility of MGs. Since the population of soft spots and their spatial distribution can be tuned by such processes as rapid quenching, 14 high-pressure torsion, [55][56][57] laser processing, 58 and mechanical cycling, 59 and magnetization, 60 we envision that our results may offer a totally new approach of using the control of short-range to medium-range order in monolithic MGs to radically improve the ductility, and hence the fracture toughness, of these alloys. As such, this may provide new possibilities for the industrial application of these high-strength metallic alloys as structural materials with unique combinations of mechanical properties.…”
Section: A Transition In Shear-band Formation Mechanismsmentioning
confidence: 98%
“…It has been suggested that the so-called local atomic shear strain, η i Mises [56], denotes the atomic motions in local regions under stress and is related to the density of shear transformations [57,58]. Meanwhile, the atomic motions probably affect the distribution of free volumes.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrostatic stress during the HPT process rejuvenates the glassy structure by increasing the free volume. At the same time the amount of local ordering and the fraction of favored five-fold motifs 24,25 is increases and is stabilized by the hydrostatic stress 5 . This effect is not present in the sample stored at room temperature after HPT.…”
Section: A Structural Characteristicsmentioning
confidence: 99%